Reflections of simulated patients on breast models as an evaluation of learning media in midwifery education - Herlyssa, Herlyssa; Wahyuni, Elly Dwi; Oktalia, Juli (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Breast models are one of the learning media used by simulated patients in midwifery care practicums. Simulated patients' perspective is a new understanding in the selection of learning media. It is hoped that the results of the reflection carried out by the simulation patient can be used for the procurement of laboratory equipment and the development of designing learning models that are lower cost but have good effectiveness. This study aims to obtain group reflections from simulation patients regarding breast models used by simulation patients for midwifery cares scenario. This research is conducted by descriptive-analytic research. The sample in this research is the total population of the simulated patients in one midwifery school in Jakarta (24 respondents). Data collection was carried out through questionnaires. There are 3 breast models. We coded these three models into A, B, and C. The research results show that based on model function indicators, model B has a better function with a mean of 4.00 compared to model A (mean 3.18) and model C (mean 3.93). Based on model design, model B is also considered to have the best design (mean 3.67) compared to models A and C. The results of this study show that the most recommended model to use is model B (91.6%), followed by model C (66.7%) and model A (50%). The simulation patient recommends that the use of breast models should meet several criteria such as ethical norms, the weight of the model, the flexible nature of the model, ease of use, and comfort, it can be combined with other learning models, and students are not afraid to use it without worrying about damaging it.